Analisa Hasil Sambungan Las ( Pipa STKM 13B Dan Plat SPH 440) Dengan Pengujian Tarik dan Photomacro - Fikri, Luqman; Simamora, Yulianto; Priyadi, Muhammad Untung Zaenal; Saleh, Yasya Khalif Perdana; Zaenudin, Mohammad; Mulyono, Sidik; Gamayel, Adhes; Triwiyanto, Askar; Jujur, I nyoman (JURNAL CRANKSHAFT, 2024)
ABSTRACTGMAW (Gas Metal Arc Welding) is a fast, versatile welding technique that can be used in various positions, but it often results porosity in welded joints.This research aims to analysis of the welded joints of STKM13B pipe and SPD 440 plate using tensile and micro testing, using welding a current of 18 and varying voltages of 110, 130, and 150. The results is the shape of the welded joint of the plate and pipe is perfectly connected, the tensile test results showed that the ultimate strength values for specimen 1, 2, 3 (A110/V18, A130/V18, A150/V18) were (18,959, 27,886, 40,005 N) respectively. The highest ultimate strength values were obtained from the specimens (A150/V18) while the lowest ultimate strength value was obtained from specimen (A110/V18). The use of welding current strongly correlates with ultimate strength value and photomacro results, with higher currents resulting in higher density levels, minimizing porosity, and increasing ultimate strength. Keywords: GMAW Welding, Tensile Test, Macro Optical Test.